Utilization of non-coherent accumulation for LTE TOA estimation in weak LOS signal environments - Jin Tian; Li Fangchi; Tian Yafei; Liu Dongmei (EURASIP Journal on Wireless Communications and Networking, 2023)
Abstract Ground localization systems based on cellular signals are vulnerable to the hazards of signal power attenuation and multipath propagation in urban environments. Non-coherent accumulation is an effective solution to this problem, but its application to cellular localization systems has not been properly discussed. In this paper, we propose two cellular time-of-arrival (TOA) estimation methods based on non-coherent accumulation: the “TOA estimation algorithm based on non-coherent accumulation of the channel impulse response” (nch-CIR) in the time domain and the “Super Resolution TOA Estimation Algorithm based on non-coherent accumulation of the covariance matrix” (nch-SRA) in the frequency domain. Among these two methods, the nch-CIR algorithm has a lower computational cost and better anti-noise performance, and the nch-SRA algorithm has better performance in terms of multipath delay estimation. Through theoretical analysis and extensive simulations, we also discuss the influence of mobility on these two methods. In addition, experiments are conducted to evaluate the performance of the proposed method using real collected cellular signals. The results show that both nch-CIR and nch-SRA can achieve a better performance compared with the conventional methods.